Analisis Strategi Pemasaran UMKM Sandal Era Digital : Studi Kasus Juan Jaya Sandals - Elsa Melani,; Lingga Yuliana, (Manajemen Kreatif Jurnal, 2024)
This study aims to analyze the marketing strategy implemented by Juan Jaya Sandals in utilizing the digital era in optimizing market potential. The study uses a qualitative method. Respondents in this study were MSME owners who adopted digital marketing, namely Juan Jaya Sandals. Primary data was used in the study using observation and interviews. The study was conducted in October 2024. The results of this study indicate that MSMEs face challenges in understanding and implementing digital marketing effectively. The managerial implications of this study are that Juan Jaya Sandals requires learning and coaching from related parties to support the sustainability of this business.